Application of Proteomics in Apical Periodontitis - Hussein, Hebatullah; Kishen, Anil (Frontiers in Dental Medicine, 2022)
Apical periodontitis is an inflammatory reaction of the periradicular tissues as a consequence of multispecies microbial communities organized as biofilms within the root canal system. Periradicular tissue changes at the molecular level initiate and orchestrate the inflammatory process and precede the presentation of clinical symptoms. Inflammatory mediators have been studied at either the proteomic, metabolomic, or transcriptomic levels. Analysis at the protein level is the most common approach used to identify and quantify analytes from diseased periradicular tissues during root canal treatment, since it is more representative of definitive and active periradicular inflammatory mediator than its transcript expression level. In disease, proteins expressed in an altered manner could be utilized as biomarkers. Biomarker proteins in periradicular tissues have been qualitatively and quantitatively assessed using antibodies (immunoassays and immunostaining) or mass spectrometry-based approaches. Herein, we aim to provide a comprehensive understanding of biomarker proteins identified in clinical studies investigating periradicular lesions and pulp tissue associated with apical periodontitis using proteomics. The high throughput mass spectrometry-based proteomics has the potential to improve the current methods of monitoring inflammation while distinguishing between progressive, stable, and healing lesions for the identification of new diagnostic and therapeutic targets. This method would provide more objective tools to (a) discover biomarkers related to biological processes for better clinical case selection, and (b) determine tissue response to novel therapeutic interventions for more predictable outcomes in endodontic treatment.